Information activities and resources in an episode of gourmet cooking - J. Hartel (Information Research: An International Electronic Journal)
Introduction. This paper contributes to what is known about everyday life information seeking within serious leisure. It is the first case study of a making and tinkering (or craft) hobby, gourmet cooking. The central activity of the hobby is described and serves as a context to relate and locate information activities and information resources. Method. In this scientific ethnography, twenty gourmet cooks from Boston and Los Angeles, USA were interviewed in their homes about their pursuit of the hobby and its associated information phenomena. Then, domestic culinary information resources and spaces were documented via a photographic inventory. Analysis. Interview transcripts and field notes were studied for themes through an iterative process of inductive and deductive analysis. A visual analysis process was performed on the photographs. Results. Hands-on cooking takes the form of a nine step episode. Information activities and resources are instrumental, interwoven, and varied across the process. In any cooking episode use and re-use are the prevailing information activities; the hobbyist is an active producer and manager of information; and the recipe is a primary document. Conclusion. The study demonstrates how to explicate and conceptualize information phenomena in serious leisure, and sets up lines of inquiry to explore in future research.